Quantitative evaluation of enterprise marketing effectiveness - Ginevičius, Adomas (Technological and Economic Development of Economy, 2007)
Enterprises operating in a complicated, constantly changing environment should pay much more attention to the market and the user, ie to marketing. Despite the fact that the main subject of the state economy is an enterprise, the problems of marketing are mostly analysed at the level of activities. At the enterprises, these problems, which are of great practical and theoretical importance, are paid little attention. One of the main problems in this context is quantitative evaluation of marketing effectiveness. The nature of the considered processes implies that this problem can be solved by multiple criteria evaluation methods. It allows us to offer a particular methodology verified by calculations. The evaluation of some actual enterprises has shown that marketing considerably affects their commercial activities in a positive way, increasing their effectiveness (profitability). Article in Lithuanian. Rinkodaros būklės įmonėje kiekybinis įvertinimas Santrauka. Aukštu kompleksiškumu pasižyminčioje, kintančioje aplinkoje įmonėms vis svarbesnis yra poreikis orientuotis į rinką ir vartotoją, t. y. savo veikloje remtis vis didesniu dėmesiu rinkodarai. Nepaisant to, kad pagrindinis šalies ūkio subjektas yra įmonė, rinkodaros klausimai daugiau nagrinėjami veiklų lygmeniu. Įmonėse jai skiriama mažai dėmesio, nors tai yra svarbi tiek praktinė, tiek mokslinė problema. Vienas svarbiausių jos klausimų – kiekybinis esamos rinkodaros būklės įvertinimas. Nagrinėjamų procesų prigimtis rodo, kad tai atlikti galima taikant daugiakriterinius metodus. Tai leido pasiūlyti atitinkamą metodiką, kuri patikrinta skaičiavimais. Realių įmonių rinkodaros vertinimas parodė, kad ji turi gana didelę teigiamą įtaką įmonių komercinės veiklos rezultatams (rentabilumas). Reikšminiai žodžiai: rinkodara, daugiakriteriniai vertinimai, komercinės veiklos rezultatai. First Published Online: 21 Oct 2010